Innovation in low-cost video-laryngoscopy: Intubator V1-Indirect compared with Storz C-MAC in a simulated difficult airway - De Villiers, Christiaan Tertius (Department of Anaesthesia and Perioperative Medicine, 2022)
Background: Video laryngoscopy has directly impacted airway management, with numerous studies demonstrating its utility in clinical management of anatomically difficult airways. However, availability of video laryngoscopes in all clinical areas has been limited by cost. We used smartphone technology, miniature cameras and three-dimensional printing to design and create an innovative low-cost hyperangulated video laryngoscope. This has the potential to make the technique more widely available. Objectives: The aim of this study was to determine if time to intubation with the novel device was clinically equivalent to an existing gold-standard video laryngoscope (Storz CMAC with Dörges blade). Methods: We conducted a randomised, controlled, cross-over equivalence study with 100 skilled practitioners who had previous video laryngoscopy experience. Participants received instruction on the new device, and adequate opportunity to practice. Intubations were then performed in a randomised order on a mannikin simulating a difficult airway. Video recordings of each intubation were analysed by two independent investigators to determine time to intubation. A mean difference in intubation time of less than 10 seconds was determined a priori to denote clinical equivalence. Results: Mean difference in intubation time between the devices was 4.92 seconds, (two one-sided test 95%CI: 2.34 – 7.49 seconds). The innovative low-cost VL was thus clinically equivalent to the industry standard in a simulated difficult airway. Further testing in vivo in a clinical environment is needed. Conclusion: The results of this study show that a low-cost disposable hyperangulated video laryngoscope is clinically equivalent to the industry standard in a simulated difficult airway. In the context of the current global pandemic, video laryngoscopy has been advised in nearly all airway guidelines. Access to a low-cost VL which does not require reprocessing may be of great value.